Book Review: Comment on a Review of Oded Stark's "Altruism and Beyond, An Economic Analysis of Transfers and Exchanges within Families and Groups" (Cambridge, New York, and Melbourne: Cambridge University Press, 1995) - Oded Stark (The Journal of International Trade & Economic Development, 1998)
There is something truly splendid about the production of a new book: as when having a child, labour is followed by birth with the child subsequently developing a life of its own. You can put into the child much, even very much, of yourself but thereafter you ought to let the child face the harsh world and not rush with assistance at every threat. That is, unless you profoundly feel that there has been a gross unfairness, in which case your urge to step in is virtually uncontrollable. In his recent review of Altruism and Beyond, An Economic Analysis of Transfers and Exchanges within Families and Groups, B.K. Kapur (1997) attributes to me assertions I did not make. In addition, he laces his review with perplexing perspectives. It is the purpose of this comment to set the record straight.
Keywords: 330